How Have New Bearing Surfaces Altered the Local Biological Reactions to Byproducts of Wear and Modularity? - Bauer, Thomas W. (Clin Orthop Relat Res, 2014)
BACKGROUND: The biologic reactions to byproducts of wear or corrosion can involve innate and adaptive processes and are dependent on many factors, including the composition, size, surface properties, shape, and concentration of debris. QUESTIONS/PURPOSES: We used a systematic literature review to compare the reported patterns of inflammation in tissues around total hip implants with the goal of identifying whether there are unique or characteristic patterns associated with the newer bearing options or modular components. METHODS: A search of the Ovid Medline database between 1996 and early December 2013 identified articles that compared the histology around six implant groups: (1) metal-on-metal; (2) ceramic-on-ceramic; (3) metal-on-crosslinked polyethylene; (4) metal-on-conventional polyethylene with or (5) without modularity; and (6) tissue obtained at primary arthroplasty. Our initial search yielded 865 citations. After excluding articles that lacked a quantitative or semiquantitative description of histologic findings in periprosthetic tissue, we reviewed 34 articles. RESULTS: No pattern of inflammation is specific for any given bearing combination. Histologic features suggestive of an adaptive immune response appear to be more frequent and of greater magnitude in failed metal-on-metal implants, but tissues around many failed metal-on-metal implants show features of an “innate” foreign body reaction without lymphocytes. Occasional nonmetal-on-metal implants show features of an immune reaction, possibly associated with metal particles. Modular connections are one source of metal debris in nonmetal-on-metal implants. Features of an immune reaction appear rare in ceramic-on-ceramic implants that lack corrosion. Insufficient reports are available to characterize the biologic response to crosslinked polyethylene. CONCLUSIONS: All total hip bearing combinations will wear in vivo, and modular interfaces are a likely source of metal that may be associated with a biological response regardless of the composition of the bearing surfaces. Surgeons must weigh the potential advantages of each articular combination and modular connection with the potential adverse tissue reactions in any given patient. Additional work is needed to clarify the implant and host-related factors associated with adverse tissue reactions and that seem to induce an immune reaction in some patients.